1966
DOI: 10.1177/14.6.455
|View full text |Cite
|
Sign up to set email alerts
|

Subcellular Localization of Rat Brain Esterases

Abstract: A 109, 000g x 60 in MICROSOME FRACTION WASH MEDIA A, 50, 000g x 120 mimi. 4BjC jD jEJ TRITON X-100 EXTRACT (for starch electrophoresis) Preparation of fractions: Male albino rats weighing 300-400 g were killed by spinal fracture, 456 BERNSOHN ET AL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

1969
1969
1978
1978

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 52 publications
(2 citation statements)
references
References 0 publications
2
0
0
Order By: Relevance
“…Short and long chain naphthyl ester substrates are hydrolysed by esterase enzymes associated with the brain myelin samples used in this work, in agreement with previous observations with myelin from other animal species (BERNSOHN et al, 1966;FREY et al, 1971). A marked specificity for the shorter chain length substrates is demonstrated in the present study.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Short and long chain naphthyl ester substrates are hydrolysed by esterase enzymes associated with the brain myelin samples used in this work, in agreement with previous observations with myelin from other animal species (BERNSOHN et al, 1966;FREY et al, 1971). A marked specificity for the shorter chain length substrates is demonstrated in the present study.…”
Section: Discussionsupporting
confidence: 93%
“…The present results demonstrate high esterase activity in the microsomal fraction of brain tissue confirming earlier observations by BERNSOHN et al (1966). In view of these findings, myelin samples were assayed further for the presence of possible microsomal contamination which could affect the esterase measurements even though our previous studies (RUMSBY et al, 1970) suggested negligible activity from other membrane structures.…”
Section: Discussionsupporting
confidence: 91%